Anti-Diabetic Activity Assessment Of Justicia Adhatoda L. Whole Plant Extract - Sivendra Pratap Singh; Dr. Alok Kumar Dash (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Objective: The objective of this experiment was to assess the antidiabetic efficacy of Justicia adhatoda L.The entire port ion of the methanol extract (JAWME) was tested for its effects on rats with Alloxan-induced hyperglycemia. Methods:Hyperglycemia was provoked by administering a dose of 150mg/kg (intraperitoneally) of alloxan monohydrat e, which had been recently dissolved in distilled water.After a period of 72 hours, the rats with a Blood Glucose Level ( BGL) higher than 150 mg/dl were chosen for the study. These rats were then separated into seven groups (IVII), each consisting of six rats. The vehicle and reference medication metformin (at a dosage of 250 mg/kg) were orally delivered to animals in group I and group II, respectively. Group III, which served as the control, received just alloxan.Groups IV, V, VI, and VII were administered methanolic extracts at doses of 100mg/kg, 200mg/kg, 300mg/kg, and 400mg/kg for 12 consecutive days. T he subjects were then observed after 1, 3, 6, and 12 days. Outcome: The ingestion of a methanolic extract at a dosage of 400mg/kg body weight demonstrated a noteworthy (*p< 0.01, **p<0.05) antihyperglycemic effect in rats with diabetes caused by alloxan.The phytochemical screening result ind icated the existence of saponins, flavonoids, alkaloids, and other compounds. Conclusion: The methanolic extract of Justicia adhatoda L demonstrates a decrease in blood glucose levels compared to the standard medication Metformin.Justicia adhatoda L has been shown to have antidiabetic properties, according to the results